Prospek dan Tantangan Dakwah Bil Qalam sebagai Metode Komunikasi Dakwah - Rini Fitria; Rafinita Aditia (JURNAL ILMIAH SYI'AR, 2019)
Communication is a process that is absolutely owned by every human beingboth verbally or non-verbally. One form of communication is called propagandacommunication. Da'wah communication is carried out for the purpose ofinviting humanity to the amar ma'ruf nahi munkar. For the purpose of thedesired da'wah communication to be achieved, a communicator must be able to choose the method to be used. Da'wah bil qalam as a method of da'wahcommunication is able to overcome the weaknesses of da'wah which is only done verbally. This method also provides the opportunity for the mad'u to choose the message of preaching in accordance with their abilities and interests so that the purpose of missionary communication is effective and efficient.